Testing the antimicrobial activity of essential oils - Frankova, Adela; Kloucek, Pavel; Smid, Jakub; Nedorostova, Lenka (Acta Agraria Debreceniensis, 2011)
The vapor phase of some essential oils proved to have antimicrobial activity. Utilization of the vapor phase of Eos is presently understood as one of the possible alternatives to synthetic food preservatives which could be used in the future. However, testing the vapor phase of EOs against microorganisms causing food-borne diseases (e.g. Salmonella enteritidis or Staphylococcus aureus) or food spoilage is relatively new. Consequently, due to the large number of known EOs, research on their antimicrobial activity is still largely in the phase of in vitro rather than in vivo testing. Moreover, no standard and reliable method for fast screening of a wide range of samples exists. Thus, the aim of this study is to show results concerning tests of the antimicrobial activity of EOs against S. enteritidis or S. aureus, which were conducted by two modifications of the disc volatilization method we developed. The lately developed method has the potential to become widely used for fast screening of EO antimicrobial activity in the vapor phase.